Alagille syndrome: from the cutaneous to the systemic (2019)
Here is reported the case of a girl with Alagille syndrome, in whom the keys to diagnosis were the dermatological manifestations characterized by chronic and persistent pruritus that led us to search for other systemic conditions, confirming the pathology.